Promoting adherence to medicines: possible lessons for Canada? - Nigel S. B. Rawson (BMC, 2017)
Abstract Non-adherence to medication regimens is a major issue that can negatively impact patient health and wastes health care system resources. This commentary considers whether approaches to strategies undertaken in Israel to promote adherence could be viable in Canada. The structure of the Canadian health care system and budgetary constraints make new initiatives similar to those in Israel seem unlikely in Canada without some compelling stimulus.